A cadaveric study on accessory lobes of lungs and their bronchial branching pattern - Krishna Kanta Biswas; Satyajit Mitra; Joydev Sarma (International Journal of Medical Research and Review, 2018)
Background: An accessory lobe is a part of lung tissue separated off by an accessory fissure. It develops due to occasional monopodial branching of the stem bronchi. Different accessory lobes may be encountered in the human lungs e.g., azygos lobe, dorsal lobe, cardiac lobe and tracheal lobe. An accessory lobe may be confused with a lung abscess or bulla in x-ray and CT-scan, and its variable bronchial supply may cause difficulty during bronchoscopy. Hence, the present work has been carried out to study the accessory lobes and their bronchial branching pattern in human lungs.Materials and Methods: 92 adult human lungs (46 right and 46 left) were collected from the Department of Anatomy and Department of Forensic and State Medicine, Gauhati Medical College and Hospital, Guwahati, Assam and preserved in 10% formalin. The lungs were, then, examined for accessory lobes and their bronchial supply was noted following dissection from the hilum.Results: In the present study, the azygos lobes were present in 2.17% of cases and dorsal lobe was present in 1.08% of cases, all of which belonged to the right side. The azygos lobes were supplied by the apical segmental bronchus of the right superior lobe and dorsal lobe was supplied by the apical basal segmental bronchus and posterior basal segmental bronchus of the right inferior lobe.Conclusion: A detailed knowledge of the accessory lobes and their bronchial supply is important for correct radiological diagnosis and bronchoscopic examination of lungs.